LTRtype, an Efficient Tool to Characterize Structurally Complex LTR Retrotransposons and Nested Insertions on Genomes - Zeng, Fan-Chun; Zhao, You-Jie; Zhang, Que-Jie; Gao, Li-Zhi (Frontiers in Plant Science, 2017)
The amplification and recombination of long terminal repeat (LTR) retrotransposons have proven to determine the size, organization, function and evolution of most host genomes, especially very large plant genomes. However, the limitation of tools for an efficient discovery of structural complexity of LTR retrotransposons and the nested insertions is a great challenge to confront ever-growing amount of genomic sequences for many organisms. Here we developed a novel software, called as LTRtype, to characterize different types of structurally complex LTR retrotransposon elements as well as nested events. This system is capable of rapidly scanning large-scale genomic sequences and appropriately characterizing the five complex types of LTR retrotransoposon elements. After testing on the Arabidopsis thaliana genome, we found that this program is able to properly annotate a large number of structurally complex elements as well as the nested insertions. Thus, LTRtype can be employed as an automatic and efficient tool that will help to reconstruct the evolutionary history of LTR retrotransoposons and better understand the evolution of host genomes. LTRtype is publicly available at: http://www.plantkingdomgdb.com/ LTRtype/index.html.